1991
DOI: 10.1111/j.1476-5381.1991.tb09849.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pinacidil on contractile proteins in high K+‐treated intact, and in β‐escin‐treated skinned smooth muscle of the rabbit mesenteric artery

Abstract: 1 The effects of pinacidil were investigated on changes in cellular Ca2+ concentration ([Ca2+]i) and tension in intact and chemically skinned smooth muscle strips of the rabbit mesenteric artery.2 High K+ (128mM) produced a large phasic followed by a tonic increase in [Ca2+]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…Chemically skinned smooth muscle strips were prepared by use of P-escin (Itoh et al, 1991). In preliminary experiments, 25 tLM P-escin was applied in an activating solution containing 10 gM Ca2+.…”
Section: Tension Measurementsmentioning
confidence: 99%
“…Chemically skinned smooth muscle strips were prepared by use of P-escin (Itoh et al, 1991). In preliminary experiments, 25 tLM P-escin was applied in an activating solution containing 10 gM Ca2+.…”
Section: Tension Measurementsmentioning
confidence: 99%
“…It was recently reported that in oc-toxintreated skinned smooth muscle strips of the rabbit mesenteric artery, a high concentration of pinacidil (100 ,tM) inhibited Ca2+-induced contraction in the presence but not in the absence of NA (Anabuki, Hori, Ozaki, Kato & Karaki, 1990). In ,-escin-treated skinned smooth muscle of the rabbit mesenteric artery, although pinacidil (10 /LM) inhibited the Ca2+-induced contraction in the presence or absence of NA (Itoh, Suzuki & Kuriyama, 1991), pinacidil (> 3 ,SM) inhibited Ca2+-induced contraction more in the presence of NA with GTP than in the absence of NA and GTP. These results suggest that a high concentration of pinacidil may directly inhibit the NA-activated hydrolysis of phosphatidylinositol-4,5-bisphosphate without its corresponding membrane hyperpolarizing action.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it was found that, in skinned vascular smooth muscle strips treated with a-toxin, phenylephrine enhanced the Ca2+ sensitivity of the contractile proteins (Nishimura, Kolber & van Breemen, 1988;Kitazawa, Kobayashi, Horiuti, Somlyo & Somlyo, 1989). Moreover, we recently reported that NAd with GTP enhanced the amplitude of contraction induced by 0 3 AM Ca2+ in /-escintreated skinned smooth muscle strips of the rabbit mesenteric artery (Itoh, Suzuki & Kuriyama, 1991 To enable simultaneous recording of isometric tension and [Ca2+]i, fine circularly cut strips (0 3-0X5 mm length, 004-0 05 mm width, 0 02-0 03 mm thickness) were prepared as previously described (Itoh et al 1983). Endothelial cells were removed by gentle rubbing of the internal surface of the vessels using small knives.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on chemically skinned smooth muscle Chemically skinned smooth muscle strips were made using /1-escin . The methods used to make skinned muscles and the composition of the solution have been described elsewhere Kobayashi et al 1989;Itoh et al 1991 For experiments on skinned muscle, the composition of the relaxing solution was: 87 mm potassium methanesulphonate (KMS), 20 mm piperazine-N-N'-bis-(2-ethanesulphonic acid) (PIPES), 5-1 mM Mg(MS)2, 5-2 mm ATP, 10 mm phosphocreatine and 4 mm ethyleneglycol-bis-(/-aminoethylether)-N,V,N',N'-tetraacetic acid (EGTA). To enable measurement of Ca2' release from skinned strips, the concentration of EGTA was reduced to 50 /tm and 2 /M Fura-2 added (as described above).…”
Section: Introductionmentioning
confidence: 99%